Una nueva especie de Cnemalobus Guerin-Meneville 1838 (Coleoptera: Carabidae: Cnemalobini) - Lagos, S.=700 1 Roig Juñent
(Es, En)
Ilus., 7 ref.
Keywords: CARABIDAE; TAXONOMIA; REGISTRO; ESPECIES NUEVAS; CHILE; CNEMALOBUS; REVISTA CHILENA DE ENTOMOLOGIA